The Impact of Missionary Type on the English Language Proficiency and Earnings of Immigrants - Nicholas Larsen; Barry R. Chiswick (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the impact of missionary activity on English language proficiency and labor market earnings of all immigrants to the United States by using the pooled files of the American Community Survey (2005-09). We consider the colonial heritage of the origin country to determine if it is a missionary effect or an effect of colonial rule. Our results suggest immigrants from countries with a high concentration of Protestant missionaries tend to exhibit higher levels of English proficiency and earnings compared to Catholic missionaries. Furthermore, a higher proficiency in English enhances earnings. One of the important implications of the findings in this paper is that a "missionary variable" often used in other studies is too aggregate and may mask important findings because of strikingly different effects of Protestant and Catholic activities.
Keywords: F22; J61; J31; J24; Z12; 330; immigrants; Protestant; Catholic; missionaries; earnings; schooling; English language; proficiency; American Community Survey